THE RELATIONSHIP BETWEEN DISTAL OCCLUSION ABOUT MORPHOLOGICAL AND FUNCTIONAL DISORDERS OF THE SPINE - O. I. Dushyna (Український стоматологічний альманах)
Analysis of contemporary publications about morphological and functional disorders of the spine and its relationship to distal occlusion become the background for this article. The aim was to study the necessity of orthodontics orthopedic diagnosis and treatment of distal occlusion.